PENERAPAN POLA NABR DAN TANGHIM DALAM MAHARAH AL KALAM MAHASISWA INDONESIA - Rosyidi, Abdul Wahab (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2016)
The study aims to reveal and explain the nabr and tanghim pattern of students’ Arabic conversation of Arabic Education Department, and to reveal the possibility of meaning change in the nabr and tanghim pattern which is mispronounced. The study is a kind of phenomenological study with a qualitative approach. Data and data sources of this research is three-semester students’ Arabic conversation of Arabic Education Department of UIN Maliki with data collection through the documentation, interview, observation, and Participation. While the data analysis technique includes comparison, segmentation, and interpretation step.The Result; that the application of nabr and tanghim patternof students’ Arabic conversation of Arabic Education Department is still many difficulties. From the conducted conversations, many idioms spoken are far from the Arabic nabr and tanghim pattern. Nabr and tanghim patterns are often mispronounced is a common phrase used in conversation though different themes, such as; wa'alaikumsalam, afwan, syukron, ahlanbiik, kaifa, madza ... While the misapplication of nabr and tanghim patterns that can lead to changes in the meaning is on the greeting wa'alaikumsalam and should be wa'alaikumussalam, which means specifically into common sense..